Impact of glucagon-like peptide 1 receptor agonist liraglutide and dipeptidyl peptidase-4 inhibitor sitagliptin on bowel cleaning and gastrointestinal symptoms in type 2 diabetes - Tong, Yan; Huang, Jian Qing; Chen, Yang; Tu, Mei; Wang, Wei (Frontiers in Pharmacology, 2023)
Abstract Objective: Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) and dipeptidyl peptidase-4 inhibitors (DPP-4i) profoundly affect the gastrointestinal motor system, which may increase the incidence of inadequate bowel cleaning and gastrointestinal symptoms. Hence, this observational study mainly aimed to assess the influence of GLP-1 RAs liraglutide and DPP-4i sitagliptin on bowel preparation in type 2 diabetes (T2DM). Method: This observational study consecutively enrolled T2DM scheduled for a colonoscopy. Participants were prospectively separated into the liraglutide group (n=120), sitagliptin group (n=120), and control group (n=120) based on the current hypoglycemic regimen. 3L split-dose polyethylene glycol regimens were used for bowel preparation. Experienced gastrointestinal endoscopists conducted colonoscopies. Lawrance Bowel-Preparation Tolerability Questionnaire and Boston Bowel Preparation Scale (BBPS) were conducted to assess bowel cleaning quality, tolerability, and safety. Results: The incidence of inadequate bowel cleaning was 17.5% in the liraglutide group, 20.5% in the sitagliptin group, and 21.7% in the control group. The difference among the three groups was not statistically significant (P=0.927). Meanwhile, there were no significant differences in the mean BBPS, cecal intubation time, and polyp-detecting rates among the three groups (all P>0.0.05). Nausea, vomiting, and bloating scores were increased in the liraglutide group compared with the other two groups (P<0.05), whereas most were mild or very mild. Subgroup analyses showed that the incidence of inadequate bowel cleaning in T2DM with DPN was increased in the liraglutide group compared with the sitagliptin group (61.3% vs. 32.1%, P=0.022) and control group (61.3% vs. 32.8%, P=0.025). Conclusion: GLP-1 RAs liraglutide or DPP-4i sitagliptin did not significantly increase the incidence of inadequate bowel cleaning and gastrointestinal symptoms during bowel preparation. Likewise, more aggressive bowel preparation regimens should be given to T2DM with DPN.